Submicroscopical features of leaves of xyris species - Sajo, Maria Das Graças [UNESP]; Machado, Silvia Rodrigues [UNESP] (FapUNIFESP (SciELO), 2001)
The leaf infrastructure of five Xyris species were examined using scanning electron microscope (SEM), transmission electron microscope (TEM) and histochemical methods. All studied leaves show some features in epidermis and mesophyll, which were of considerable adaptative significance to drought stress. Such features included the occurrence of a pectic layer on the stomatal guard cells and the presence of a nehvork ofpectic compounds in the cuticle. Pectic compunds were also in abundance in lamellated walls of the mesophyll cells and on the inner surface of the sclerified cell walls of the vascular bundle sheaths. There were also specialized chlorenchymatous peg cells in the mesophyll and drops of phenolic compounds inside the epidermal cells.
Keywords: Leaf; Ultrastructure; Xyris